Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1981
DOI: 10.1128/jb.148.1.283-293.1981
|View full text |Cite
|
Sign up to set email alerts
|

Influence of lipopolysaccharide and protein in the cell envelope on recipient capacity in conjugation of Salmonella typhimurium

Abstract: In crosses of Salmonella typhimurium FfinP301 lac+ to F- strains of S. typhimurium in broth, recipient strains which were rough mutants affected in the outer core region of the lipopolysaccharide gave an average of 1.4 Lac+ transconjugants per donor cell and over 50% of the donor and recipient cells in mating aggregates, whereas smooth recipient strains gave 0.08 Lac+ transconjugants and few cells in mating aggregates. Strains with mutations affecting the inner core of the lipopolysaccharide were usually poor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…For example, in Enterococcus faecalis, potential recipients secrete signalling peptides that induce conjugation of certain plasmids (Dunny et al, 1978;Dunny, 2013). Studies with Escherichia coli, Salmonella typhimurium and E. faecalis identified surface components of the recipient that facilitate formation of mating pairs and contribute to conjugation (Watanabe et al, 1970;Skurray et al, 1974;Havekes et al, 1977;Sanderson et al, 1981;Trotter and Dunny, 1990;Ishiwa and Komano, 2004;Perez-Mendoza and de la Cruz, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Enterococcus faecalis, potential recipients secrete signalling peptides that induce conjugation of certain plasmids (Dunny et al, 1978;Dunny, 2013). Studies with Escherichia coli, Salmonella typhimurium and E. faecalis identified surface components of the recipient that facilitate formation of mating pairs and contribute to conjugation (Watanabe et al, 1970;Skurray et al, 1974;Havekes et al, 1977;Sanderson et al, 1981;Trotter and Dunny, 1990;Ishiwa and Komano, 2004;Perez-Mendoza and de la Cruz, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Van Leeuwen pers.comm.). The F'-plasmid in strain SA2197 was derepressed with regard to fertility inhibition by the pSLT plasmid resident in LT2-strains (Sanderson et al 1981).…”
Section: Materials and Methods B A C T E R I A L H O S T S T R A I N mentioning
confidence: 99%
“…Model experiments have shown that group E phages are capable of surviving well in water and sewage treatment processes (Ayres 1977) and that they are relatively resistant to inactivation by disinfectants (Shah & McCamish 1972;Snead el a!. 1980), heat treatment (Burge et ul.…”
mentioning
confidence: 99%
“…The genetic organization of mobile DNA elements such as plasmids and bacteriophages differs from the chromosomal Bradley & Cohen (1976), Sanderson et al (1981), Gotz et al (1996) Ernstsson et al (2003) organization of their hosts. Plasmid organization, reviewed in detail by Thomas (2000), is based on the confluence and clustering of different survival and propagation functions, arranged in functional modules.…”
Section: Introductionmentioning
confidence: 99%